Prevalence of Mineral Bone Disease in Dialysis Patients - Rizvi, Nabiha; Tasleem, Faiza; Altaf, Ulfat (Pakistan Journal of Kidney Diseases, 2021)
Progressive loss of kidney function in chronic kidney disease (CKD) leads to reduced production of 1-α-(OH)2-D3 (1,25-dihydroxyvitamin D; calcitriol) and abnormal mineral homeostasis leading to bone mineral disorders. The disorder starts with stage 2 CKD but manifests itself as the disease progresses until stage 3 CKD. Material and methods This study was carried out on 61 patients with end-stage renal disease on regular HD at our Centre. After obtaining informed consent, complete blood count, blood urea level, serum creatinine level, albumin level, uric acid level, Ca level, phosphate level, alkaline phosphatase level, and PTH level were done. Results Out of 60 patients 41 (68.33%) were high bone turnover,10 (16.6%) were normal bone turnover whereas 9(15%) were low bone turnover. Conclusion The prevalence of CKD-MBD among dialysis patients is 83.33% at our center and needs proper monitoring by routine investigations including serum phosphate, calcium, vitamin D levels and most importantly i-PTH levels according to guidelines.